A New Shaft Kiln For Lime Production - Charles E. Dandois; Whitmell J. Smithwick (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
The first operating unit of the ring or annular shaft kiln as developed by Mr. Karl Beckenbach of West Germany was rated 185 tpd and was installed in 1962. Today, there are approximately 84 units in operation in Western Europe and Japan. Twenty-one additional units are under construction or on order. Sizes range from approximately 100-330 tpd, however, units of over 500 tons are in the design stage. The ring shaft kiln is a single vertical cylinder to which are attached the required service platforms, combustion chambers, injectors and distribution piping (Fig. 1). Auxiliaries such as recuperator, exhaust fan and dust collector are mounted on the appropriate service platform. The charging pan, feed conveyor, etc., are mounted at the kiln top and at the bottom of the kiln is the silo with a vibrator type discharger. Mounted separately is the required blower for injector air and fan for internal cooling.